A Comparative Study on Short-term Clinical Outcome in Acute Coronary Syndrome - Sultana, Syeda Aleya; Iqbal, Syed Asif; Malek, Md Abdul; Rahman, Md Wali ur; Alam, Abu Yusuf Md Shahidul; Haque, Md Aminul; Rabbani, Safia Binte (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Coronary artery diseases are currently the major cause of death in developing countries. Acute coronary syndrome (ACS) is defined as any group of clinical symptoms compatible with acute myocardial ischemia and covers the spectrum of clinical conditions ranging from unstable angina (UA) to non-ST elevation myocardial infarction (NSTEMI) to STelevation myocardial infarction (STEMI). Accurate diagnosis and management of ACS has life-saving implications of its outcome. Objective: To compare the outcomes of STEMI and NSTEMI in a percutaneous coronary intervention (PCI) capable centre. Materials and Methods: The patients who undergone percutaneous coronary intervention (PCI) in Combined Military Hospital, Dhaka were considered from January 2013 to January 2017. Diagnosis of acute MI was based on the clinical presentation, electrocardiogram (ECG) and raised highly sensitive troponin I. Acute MI patients were classified into 2 groups, STEMI and NSTEMI. Their coronary risk factors, co-morbidity, ECG, echocardiogram, coronary angiographic (CAG) findings and short-term outcomes were collected. All statistical data were analysed by SPSS 22.0 software. Results: There were 464 patients enrolled for analysis. Among them, 208(44.8%) patients had STEMI and 256(55.2%) had NSTEMI. The ratio of male/female was greater in STEMI as compared to NSTEMI (4.0 vs 1.9; p=0.041). Among NSTEMI patients, 88(34.4%) had ST depression, 168(65.6%) patients had other ECG changes like T wave abnormalities in 66(25.7%) and poor R-wave progression in 16(6.3%). NSTEMI patients had less regional wall motion abnormality on echo cardiogram (p=0.0045). As a complication heart failure (36% vs 9.3%), cardiogenic shock (16.8% vs 15.6%), atrial fibrillation (7.2 vs 0.78 %), ventricular tachycardia (2.8% vs 0.5%), reinfarction (3 % vs 0.78%) and death (2.4% vs 0.40%) were observed more in STEMI patients than NSTEMI respectively. NSTEMI patients had less regional wall motion abnormality on echocardiogram (p=0.0045). As a complication heart failure (36% vs 9.3%), cardiogenic shock (16.8% vs 15.6%), atrial fibrillation (7.2% vs 0.78%), ventricular tachycardia (2.8% vs 0.5%), reinfarction (3% vs 0.78%) and death (2.4% vs 0.40%) were observed more in STEMI patients than NSTEMI respectively. Coronary angiogram shows that left anterior descending artery was the most commonly involved artery in STEMI; however, the left circumflex artery or right coronary artery was involved more commonly in NSTEMI (p<0.001). Conclusion: The first step in successful treatment of acute MI depends on early diagnosis. Inspite of immediate management, STEMI had relatively worse outcome compared to NSTEMI. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 22-27